Analysis of Factors Influencing the Incidence of Urinary Incontinence in Elderly Women in Medan - Meena Agusma; Nurmaini Nurmaini; Cholina Trisa Siregar (Jurnal Berita Ilmu Keperawatan, 2023)
Urinary incontinence is a serious health problem that is very vulnerable to be experienced by the elderly caused by urinary disorders, especially women who can increase the risk of postpartum infection. This study used an observational analytic study with astudy design case control with aapproach. A retrospective approach was used to see how many factors were diabetes mellitus, hypertension, parity, mode of delivery, history of hysterectomy surgery, history of gynecological surgery, menopause, body mass index (BMI) and education towards the effect of urinary incontinence in the case group and control group in elderly women in Medan. The results of the study based on the results of statistical tests obtained p value > 0.05 indicating that there was no effect of increasing body weight on the incidence of urinary incontinence. In the blood sugar level variable, the p value <0.05 showed that there was an effect of blood sugar levels on the incidence of urinary incontinence with an OR = 4.375 (95% Cl; 1.320-14.504). blood pressure on the incidence of urinary incontinence with a value of OR = 4.250 (95% Cl; 0.507-9.993), the variable history of delivery obtained p value <0.05 there is an effect of mode of delivery on the incidence of urinary incontinence with an OR value of 4.190 (Cl 95%; 0.716-6.698), the parity variable obtained p value > 0.05, there was no effect of the number of parity on the incidence of urinary incontinence, the variable length of menopause obtained p value > 0.05 indicating that there was no effect of the length of menopause on the incidence of urinary incontinence, on the history of hysterectomy variable obtained p value <0.05, there is an influence between the history of hysterectomy surgery on the incidence of urinary incontinence with OR = 2.740 (95% Cl; 0.252-2.175), on the variable r gynecological history Statistical test results obtained p value > 0.05 indicating that there is no effect between the history of geniculate surgery on the incidence of urinary incontinence